Diagnostic and clinical utility of next‐generation sequencing in children born with multiple congenital anomalies in the China neonatal genomes project. Issue 4 (4th February 2021) - Wang, Huijun; Xiao, Feifan; Dong, Xinran; Lu, Yulan; Cheng, Guoqiang; Wang, Laishuan; Lu, Wei; Yang, Lin; Chen, Liping; Kang, Wenqing; Li, Long; Pan, Xinnian; et al.
Abstract: Multiple congenital anomalies (MCAs) at birth have emerged as an important cause of neonatal morbidity and mortality. This study aimed to investigate the genetic causes and characteristics of clinical outcomes in a large cohort of neonates with MCAs. Clinical exome sequencing/exome sequencing/genome sequencing were undertaken from December 1, 2016 to December 1, 2019 to detect single nucleotide variations (SNVs) and copy number variations (CNVs) simultaneously in individuals who met the inclusion criteria. A total of 588 neonates with MCAs were enrolled. One hundred sixty‐one patients received diagnosis, with 71 CNVs and 90 SNVs detected, the overall diagnostic rate being 27.38%. Cardiovascular malformation was the most common anomaly (60%) and accounted for the top symptomatic proportion in both CNVs and SNVs. As the number of involved system increased from 2 to 3–4, and then to ≥5, the overall diagnostic rate increased gradually from 23.1% to 30.5%, and then to 52.2%, respectively. Patients who received genetic diagnoses were offered better clinical management or were referred to the specific disease clinic. In conclusion, this large cohort study demonstrates that both CNVs and SNVs contribute to the genetic causes of MCAs, and earlier genetic assertion may lead to better clinical management for patients.